The Effectiveness of Instagram Ads and Facebook Ads as Promotional Platforms in Room Sales at Fairfield by Marriott Bali Legian - Wiguna, I Komang Bintang Tri; Suastini, Ni Made; Pitanatri , Putu Diah Sastri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effectiveness of Instagram ads and Facebook ads as a promotional platform in selling rooms at Fairfield by Marriott Bali Legian. This type of research is quantitative. The sample used was 100 respondents. The data was analyzed using the EPIC Model, average scores and simple tabulations to measure the effectiveness of Instagram ads and Facebook ads. The results of this study indicate that the score for each dimension of the EPIC Model is in the range of a fairly effective scale. Namely between 2.60-4.40, the scores for each dimension are: (a) the empathy dimension has a score of 2.18, (b) the persuasion dimension has a score of 2.31 (c) the impact dimension has a score of 3.75, (d) the communication dimension has a score of 3.08, The final result obtained based on the overall EPIC Rate is 2.83 which is in the range of a fairly effective scale